Condyloma acuminata in the tongue and palate of a sexually abused child: a case report - Percinoto, Ana Clélia Cânovas (BioMed Central, 2014)
BACKGROUND: Condyloma acuminata caused by human papilloma viruses, (HPV) is a sexually transmitted disease (STD) appearing most frequently as soft, pink cauliflower like growths in moist areas, such as the genitalia, mouth and other places. The disease is highly contagious, can appear singly or in groups, small or large. In children, the isolation of a sexually transmitted organism may be the first indication that an abuse has occurred. Although the presence of a sexually transmissible agent from a child beyond the neonatal period is suggestive of sexual abuse, exceptions do exist. CASE PRESENTATION: The authors report the clinical case of a five-year-old Caucasian male with lesions located in the dorsal surfaces of the posterior tongue and palate. Both lesions had a firm consistency, reddish appearance and presence of whitish areas and regions of ulceration. During the interview, the mother reported that the boy had been sexually abused. CONCLUSION: Sexually transmitted disease may occur during sexual abuse. Dentists as well as pediatricians have a role to play in identifying and treating these children. The diagnosis is essentially clinical (anamnesis and physical examination), but also the use of cytology eventually resorts to biopsy of the suspicious lesions for histological examination. The therapeutic option was the excision of the lesions.